Tanaman Obat Tradisional Dusun Dlingo Kecamatan Geyer Grobogan, Jawa Tengah - Tita Nopiyanti; Santhyami Santhyami; Zozy Aneloi Noli; M. Idris (Jurnal Biosilampari : Jurnal Biologi, 2025)
Indonesia is renowned for its rich diversity of medicinal plants, and traditional knowledge of herbal medicine remains deeply rooted in many local communities. In Dusun Dlingo, Grobogan Regency, Central Java, residents continue to rely on medicinal plants as a form of alternative treatment. However, the rapid advancement of technology and modernization poses a significant threat to the preservation of this traditional knowledge, particularly among younger generations. This study aims to identify and document the various types of medicinal plants recognized and used by the Dlingo community. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation. This research revealed 35 species used as traditional remedies from 21. These include 8 species from the Zingiberaceae family, 3 species from the Apiaceae family, 3 species from the Piperaceae family, 2 species from the Fabaceae family, and 2 species from the Malvaceae family. The highest proportion of medicinal plants is used as tonics, with 7 species identified.